Development of Detection and Flood Monitoring via Blynk Apps - Mahanijah Md Kamal; Nur Anum Zuraimi Md Noar; Aqil Muhammad Sabri (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
Flash flood is a common disaster event occured at Jalan Ilmu 1/1, Universiti Teknologi MARA Shah Alam Campus when there is a heavily raindrops. This paper describes the development of prototype used for detection and monitoring purposes. Flash floods can lead to destruction of properties and infrastructures.This system is based on two NodeMCU based technology integrated using Blynk application (IOS or android). The wireless sensor network systems can help the citizens by detecting the water levels and give an early warning when a flood occurs faster and easy. Basically, there are two part of the system which are the sensor node and the base station. The sensor node detects the water level using an ultrasonic sensor and display the current water level.The first NodeMCU is placed at the identified flood area, whilst the second NodeMCU acts as the control unit. Data detected from the ultrasonic sensorsare sent to the Blynk application via wireless connection.Two test have been conducted to test the effectiveness of the propose system. It can be found that this prototype able to detect, monitor and give alarm to the affected area if the flash flood happens in the future.